A dynamic structural framework for the allosteric regulation of Hsp70 chaperones - Rohland, Lukas; Kityk, Roman; Smalinskaitė-Wolf, Luka; Lashkul, Veronika; Mayer, Matthias P. (The journal of biological chemistry, 2025)
Central to allosteric signaling mechanisms are three processes: (I) initial sensing of the allosterically active ligand, (II) allosteric signal relaying from the ligand binding pocket to the allosterically affected parts of the protein, and (III) stabilization of the allosterically activated state. Hsp70 proteins are ATP-driven molecular chaperones that are essential in many organisms across the tree of life and exert their action using an intricate allosteric mechanism. Although pathways of this allosteric signaling mechanism have been outlined, its spatiotemporal organization is poorly understood. Here, we present the structural and dynamic basis of these allosteric signaling pathways for the prokaryotic model Hsp70 DnaK that rationalizes the action of ATP, several of its analogues, and clients on the allosteric signal transmission. Our data reveal that during the initial sensing of ATP, DnaK tolerates chemical alterations in the α-phosphate group of ATP but not in the γ-phosphate group. Amino acid replacements that interfere with the allosteric regulation of DnaK disrupt the ATP-induced relay of allosteric signal transmission at specific steps by altering the mechanics of allostery or the stability of reaction intermediates, or both. Client binding to a DnaK variant that is unreceptive to the client-sent signals that stimulate DnaK’s ATPase activity, also shows diminished client-induced conformational remodeling of ATP-bound DnaK, suggesting that client-induced conformational changes in DnaK are needed to trigger ATP hydrolysis. Based on these observations, we formulate a dynamic structural framework for the allosteric regulation of Hsp70 chaperones, linking the molecular mechanics of Hsp70s to their biochemical properties.
Online veröffentlicht am 24. Juli 2025
Gesehen am 18.02.2026